Pengembangan game edukasi pokpok: grab the garbage untuk menanamkan nilai peduli lingkungan peserta didik SD Negeri Kotagede 4 Yogyakarta - Atika Puspita Dewi; Retno Utaminingsih; Murniningsih Murniningsih (Universitas Sarjanawiyata Tamansiswa, 2026)
The issue found in the field shows that students still litter and do not understand how to properly sort waste. This study aims to (1) develop an educational game “PokPok: Grab the Garbage” to instill environmental care values in students of SD Negeri Kotagede 4 Yogyakarta, (2) test the feasibility of the game, and (3) describe the responses of teachers and students to the game. The research employed a Research and Development (R&D) method using the ADDIE model which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through structured interviews, questionnaires, and documentation. Instruments included interview guides, expert validation sheets, and user response questionnaires. The subjects were fourth-grade students, and the object of research was the “PokPok: Grab the Garbage” educational game. Quantitative data and interview results were analyzed descriptively. The results show that the game was developed through all five ADDIE stages. Media and material experts gave average feasibility scores of 4.42 and 4.54, categorized as very good. User responses averaged 4.19 (teachers) and 4.66 (students). These findings indicate that the game is feasible and effective for instilling environmental care values in an interactive and fun way.